Analysis of Consumer Behavior Factors in Purchasing Woven Bag Craft Products in the Perspective of Maqāṣid Al-Sharīʿah (Case Study of Presidio Village, Grabag District, Magelang Regency) - Fadilah, Puji Nur; Pudail, M.; Alfiyanto, Achmad Nur (Universitas Alma Ata, 2023)
Behind a large number of enthusiasts and the increase in handicraft businesses, various kinds of consumer behavior occur when the process of purchasing a product, for example, consumer behavior in assessing or comparing the advantages of one product to another. Consumer behavior is a destination instrument where consumer behavior will be directed. Consumer behavior is a preference that is relative by characterizing one's experience in interacting with several objects. The purpose and benefits of this research are to find out consumer behavior, what are the reasons and motivations for consumers in making purchasing decisions for handicraft products from the perspective of Maqosid Syariah so that in the future they can better manage strategies in developing businesses. This study used a type of qualitative research. The research data is primary data and secondary data obtained directly by informants at the location of the object of research including woven bag craft business owners, consumers, and the community in Presidio Village, Grabag District, Magelang Regency